Pemikiran Keagamaan di Indonesia (Analisis terhadap Pemikiran Tradisionalisme dan Modernisme Islam) - Muhammad Taufan Djafri; Andi Muh. Taqiyuddin BN; Muhammad Saleh Tajuddin; Hamzah Harun Al Rasyid (AL-QIBLAH: Jurnal Studi Islam dan Bahasa Arab, 2023)
This study aims to determine religious thought in Indonesia based on an analysis of Islamic traditionalism and modernism. This research is a library research using a comparative descriptive approach. The research method used is a qualitative research method. The results of the research show that in the thinking of Islamic traditionalism and modernism there are differences that have created conflict. Nonetheless, the conflicts and differences that occur are only on methodological issues in approaching Islamic teachings such as furū`iyyah issues and do not extend to issues that are fundamental in nature.